2007
DOI: 10.1094/ats-2007-0702-01-rs
|View full text |Cite
|
Sign up to set email alerts
|

Single Fall Applications of Coated Urea Fertilizers Produce a High Quality Kentucky Bluegrass Turf

Abstract: Kentucky bluegrass (Poa pratensis L.) lawns generally require N fertilizer at 98 to 196 kg/ha/year to maximize appearance and growth. Most homeowners do not regularly fertilize, resulting in weed‐ and disease‐prone lawns due to insufficient N. This two‐year field study evaluated three urea‐based N sources: urea, sulfur‐coated urea (SCU), and polymer‐coated urea (PCU) at N rates of 0, 49, or 147 kg/ha/year applied in early September only or 49 kg/ha/month from September through November. Mean turfgrass quality,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
6
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 26 publications
1
6
0
Order By: Relevance
“…Results from this study demonstrate the quality and color benefits of late‐fall N applications on creeping bentgrass putting greens, supporting the findings cited in other research for northern environments (Powell et al, 1967b; Wilkinson and Duff, 1972; Ledeboer and Skogley, 1973, Wehner et al, 1988; Wehner and Haley, 1993; Miltner et al, 2004; Grossi et al, 2005; Mangiafico and Guillard, 2006; Bigelow et al, 2007). Ammonium sulfate applications from the end of September to mid‐October, with soil temperatures near 10°C, were effective in producing positive turfgrass quality and color responses in the fall; higher rates (up to 50 kg N ha −1 ) increased these effects.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Results from this study demonstrate the quality and color benefits of late‐fall N applications on creeping bentgrass putting greens, supporting the findings cited in other research for northern environments (Powell et al, 1967b; Wilkinson and Duff, 1972; Ledeboer and Skogley, 1973, Wehner et al, 1988; Wehner and Haley, 1993; Miltner et al, 2004; Grossi et al, 2005; Mangiafico and Guillard, 2006; Bigelow et al, 2007). Ammonium sulfate applications from the end of September to mid‐October, with soil temperatures near 10°C, were effective in producing positive turfgrass quality and color responses in the fall; higher rates (up to 50 kg N ha −1 ) increased these effects.…”
Section: Discussionsupporting
confidence: 89%
“…The efficiency of 25-and 50-kg N ha −1 applications was similar under optimum weather conditions, but this efficiency was reduced in environments conducive to N loss and reduced plant uptake; precipitation, and cold temperatures. The most efficient use and consistent benefit was seen with the spoon-feeding approach Wilkinson and Duff, 1972;Ledeboer and Skogley, 1973;Wehner et al, 1988;Wehner and Haley, 1993;Miltner et al, 2004;Grossi et al, 2005;Mangiafico and Guillard, 2006;Bigelow et al, 2007), increased rooting (Hanson and Juska, 1961;Powell et al, 1967a;Moore et al, 1996), and an increase in carbohydrates (Schmidt and Shoulders, 1971). Powell et al (1967b) first reported the benefits of late-fall N fertilization of cool-season turfgrass.…”
mentioning
confidence: 94%
See 1 more Smart Citation
“…With respect to different N forms, slow‐release sources may yield different turfgrass growth and color responses than the straight urea used herein. However, under similar rates or at higher rates, few meaningful differences in turfgrass reflectance values between different N sources have been reported (Bigelow, Walker, & Hardebeck, 2007; Brede & Bartell, 2009; Trenholm & Unruh, 2005). On shorter‐cut golf turf, reflectance differences were reported between amine and salt formulations of liquid N fertilizers (Zhu et al., 2012; Zhu, Schlossberg, & Bryant, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…The environmental and economic sustainability of professional turfgrass management rely heavily on operational efficiency. Thus, stakeholders maintain a keen interest in realizing cost benefits from technology supporting extended nutrient availability following a single, yet sizable, fertilizer application to turfgrass systems either late or early in the growing season [28].…”
Section: Introductionmentioning
confidence: 99%